On the catalytic mechanisms of lytic polysaccharide monooxygenases. (April 2016) - Walton, Paul H; Davies, Gideon J
Highlights: Lytic polysaccharide monooxygenases are newly discovered copper oxygenases. LPMOs open up new thinking about oxidation mechanisms. Copper histidine brace active site is challenging precepts in bioinorganic chemistry. The catalytic mechanism of LPMOs is an area of intense study. LPMOs are important factors in commercial biofuel production. Abstract : Lytic polysaccharide monooxygenases (LPMOs) are recently discovered copper-containing oxygenases. LPMOs oxidise recalcitrant polysaccharides such as chitin and cellulose, thereby making these substrates more tractable to canonical chitinase or cellulase action. As such, LPMOs are attracting much attention not only for their capacity to greatly increase the efficiency of production of cellulosic-based biofuels, but also for the new questions they pose about the mechanisms of biological oxidation of recalcitrant substrates. This review draws together the current thinking on the catalytic mechanisms of LPMOs and other copper catalysed oxygenations and provides a blueprint for further investigation into the mechanisms of action of these intriguing enzymes.